ByzRev 02.2020.027: Alexander Riehle (ed.), A Companion to Byzantine Epistolography: (Brill’s Companions to the Byzantine World 7). Leiden – Boston: Brill 2020. - Mullett, Margaret (The Byzantine Review, 2020)
Alexander Riehle (ed.), A Companion to Byzantine Epistolography (Brill’s Companions to the Byzantine World 7). Leiden – Boston: Brill 2020. xii+531 pp. – ISBN: 978-90-04-41369-6 (€ 238,00)